2019
DOI: 10.1002/brb3.1381
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal associations between job strain and depression: A 2‐year follow‐up study from the Survey of Health, Ageing and Retirement in Europe

Abstract: Background A growing number of people suffered from depression. This study examined the depression prevalence in workers across 10 European countries plus Israel and the reciprocal associations between job strain and depression. Methods The study population consisted of 7,879 workers aged 50–63 years at baseline (2004) from the Survey of Health, Ageing, and Retirement in Europe (SHARE). Job demands (physical or psychosocial) and job control variables were derived from the Job Content Questionnaire (JCQ). Two 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Marital status was obtained by asking the participants: "What is your marital status?" and living arrangement by the question: "Do you have a partner who lives outside this household?," these two variables were integrated into one and was categorized into living with a partner (married and living with spouse or registered partnership in the same household) and living alone (married but not living with spouse, never married, divorced, or widowed) as in previous studies [51].…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Marital status was obtained by asking the participants: "What is your marital status?" and living arrangement by the question: "Do you have a partner who lives outside this household?," these two variables were integrated into one and was categorized into living with a partner (married and living with spouse or registered partnership in the same household) and living alone (married but not living with spouse, never married, divorced, or widowed) as in previous studies [51].…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…In contrast, a higher prevalence of depression was present among workers 50-63 years participating in the SHARE study, although with high variability among European countries, ranging from 12% in Germany to 27% in France (Qiao et al, 2019). Another study combining data from SHARE and ELSA estimated an overall prevalence of depressive symptoms of 14% among workers 50-64 years (Siegrist et al, 2012), similar to that observed in a Swedish study (Nyberg et al, 2019).…”
Section: Healthmentioning
confidence: 50%
“…A corresponding pathway seems reasonable with respect to the association between the partner’s job demands and one’s own depressive symptoms. Studies have shown that physical work can increase the stress [ 46 ] and damage the mental health [ 47 ] of an individual, and that such developments can lead to increased depressive symptoms for the individual’s partner, more particularly among women [ 10 , 48 ].…”
Section: Discussionmentioning
confidence: 99%